2021
DOI: 10.1016/j.xnsj.2021.100083
|View full text |Cite
|
Sign up to set email alerts
|

The effect of instrumentation staging on patient outcomes in pyogenic vertebral osteomyelitis: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…The overall mortality rate (3%) in this cohort study was lower or in line compared to other reports ( Ackshota et al, 2019 ; Shiban et al, 2014 ; Sanda et al, 2021 ; Vettivel et al, 2019 ; Zarghooni et al, 2012 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall mortality rate (3%) in this cohort study was lower or in line compared to other reports ( Ackshota et al, 2019 ; Shiban et al, 2014 ; Sanda et al, 2021 ; Vettivel et al, 2019 ; Zarghooni et al, 2012 ).…”
Section: Discussionsupporting
confidence: 84%
“…Surgical debridement aims to decrease the infectious load and therefore may lower the rate of infection recurrence. While other studies show very diverse results concerning relapse rate, the rate of recurrence and relapse in this surgical cohort was 9% ( Shiban et al, 2014 ; Sanda et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 57%
“…Both internal fixation and bone fusion are reported to be performed safely in the presence of infection [ 15 ]. Whereas Sanda et al [ 16 ] reported that patients with instrumentation have higher rates of reinfection than those with the surgical treatment but without fixation, indicating there may be an increased risk of reinfection due to bacteria on the instrumentation.…”
Section: Discussionmentioning
confidence: 99%